2022
DOI: 10.1177/09721509221125576
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Green Supply Chain Management Practices on Firm Performance: Evidence from Manufacturing Industry

Abstract: Global climate change, environmental pollution and depleting natural resources have necessitated major changes in the way businesses undertake procurement, manufacturing, operations and provision of goods and services to customers. Therefore, green supply chain management (GSCM) practices have caught the attention of researchers in many different countries. However, the adoption of GSCM practices and their influence on firm performance is still in its early stages. This study examines the influence of GSC dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…In addition, Afzal and Hanif [100] note that green supply chain initiatives, excluding green purchasing, positively impact firm performance, highlighting the significance of environmental practices. Ullah et al [101] demonstrate that implementing green supply chain management (GSCM) practices allowed companies to recover from economic downturns caused by the COVID-19 pandemic, highlighting the advantageous resilience of green practices.…”
Section: Green Logistics Management Practices and Supply Chain Resili...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Afzal and Hanif [100] note that green supply chain initiatives, excluding green purchasing, positively impact firm performance, highlighting the significance of environmental practices. Ullah et al [101] demonstrate that implementing green supply chain management (GSCM) practices allowed companies to recover from economic downturns caused by the COVID-19 pandemic, highlighting the advantageous resilience of green practices.…”
Section: Green Logistics Management Practices and Supply Chain Resili...mentioning
confidence: 99%
“…Liu and Wei [98] demonstrate how supply chain risk management analytics enables organizations to quickly adjust to disruptions, which aligns with the dynamic capabilities theory's focus on strategically reconfiguring in response to environmental changes. The studies by Ahmad et al [99] and Afzal and Hanif [100] look at how green supply chain management (GSCM) practices can help turn green innovation strategies into better long-term and overall firm performance.…”
Section: Green Logistics Management Practices As a Mediatormentioning
confidence: 99%
“…The result showed that environmental regulation has no negative effect in most of industries. Afzal and Hanif (2022) believed that environmental pollution and natural resource consumption made manufacturing enterprises have to undergo significant changes. The results show that green supply chain management has a significant impact on the performance of manufacturing enterprises.…”
Section: Influencing Factors Of Industrymentioning
confidence: 99%
“…Most of the previous literatures were studied UID from a single perspective, such as finance (Xu and Pal, 2022), environment (Afzal and Hanif, 2022;Lena et al, 2022) and technology (Dos Santos et al, 2020;Xie et al, 2021). Few scholars study UID from multi-dimensions.…”
Section: Theoretical Implicationmentioning
confidence: 99%